2023
DOI: 10.3390/agronomy13092405
|View full text |Cite
|
Sign up to set email alerts
|

Role of Melatonin in Directing Plant Physiology

Karthikeyan Ramasamy,
Kalarani M. Karuppasami,
Senthil Alagarswamy
et al.

Abstract: Melatonin (MT), a naturally occurring compound, is found in various species worldwide. In 1958, it was first identified in the pineal gland of dairy cows. MT is an “old friend” but a “new compound” for plant biology. It brings experts and research minds from the broad field of plant sciences due to its considerable influence on plant systems. The MT production process in plants and animals is distinct, where it has been expressed explicitly in chloroplasts and mitochondria in plants. Tryptophan acts as the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 209 publications
0
0
0
Order By: Relevance
“…Studies have reported that exogenously applied MT and endogenous MT synthesized by the plant itself act in the same way, and both increase the tolerance of plants to stress [12]. Numerous studies have demonstrated that endogenous MT, as well as the application of exogenous MT, regulates various physiological and metabolic processes in plants [13] and is involved in the response to adverse abiotic stresses [14,15]. In oat, MT upregulates antioxidant genes and improves the photosynthetic capacity under osmotic stress [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that exogenously applied MT and endogenous MT synthesized by the plant itself act in the same way, and both increase the tolerance of plants to stress [12]. Numerous studies have demonstrated that endogenous MT, as well as the application of exogenous MT, regulates various physiological and metabolic processes in plants [13] and is involved in the response to adverse abiotic stresses [14,15]. In oat, MT upregulates antioxidant genes and improves the photosynthetic capacity under osmotic stress [16].…”
Section: Introductionmentioning
confidence: 99%